2021
DOI: 10.1016/j.csbj.2021.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium ions regulate mesenchymal stem cells population and osteogenic differentiation: A fuzzy agent-based modeling approach

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 78 publications
2
20
0
Order By: Relevance
“…Thus, a stronger effect of magnesium pyrophosphate on cellular activity could be observed after seeding of cells on cement surfaces, but on the other hand, this effect needs to be thoroughly analyzed as the accuracy of the results can be affected by incorrect surface structure. Numerical simulation to predict cellular processes verified experimental data on the stimulatory effect of Mg at 3–6 mM concentration on proliferation and ALP activity as well as OC inhibition as a late differentiation marker of MSCs [ 61 ], but this level was not reached in C1MP or C2MP cement extracts; however, the local ion concentration may be higher in close contact between cements and cells or tissues. Magnesium (3 mM) was found to be able to effectively reduce β-glycerol phosphate-induced calcification in rat vascular smooth muscle cells by regulating ALP and OP gene expression [ 62 ].…”
Section: Discussionmentioning
confidence: 79%
“…Thus, a stronger effect of magnesium pyrophosphate on cellular activity could be observed after seeding of cells on cement surfaces, but on the other hand, this effect needs to be thoroughly analyzed as the accuracy of the results can be affected by incorrect surface structure. Numerical simulation to predict cellular processes verified experimental data on the stimulatory effect of Mg at 3–6 mM concentration on proliferation and ALP activity as well as OC inhibition as a late differentiation marker of MSCs [ 61 ], but this level was not reached in C1MP or C2MP cement extracts; however, the local ion concentration may be higher in close contact between cements and cells or tissues. Magnesium (3 mM) was found to be able to effectively reduce β-glycerol phosphate-induced calcification in rat vascular smooth muscle cells by regulating ALP and OP gene expression [ 62 ].…”
Section: Discussionmentioning
confidence: 79%
“…By contrast, higher Mg concentrations appeared cytotoxic [ 51 , 52 ]. Of note, a recent reported computer model, calibrated using experimental data, showed that Mg ions within the range of 3–6 mM increased proliferation and early differentiation, whereas high levels caused deleterious effects [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, an increasing number of studies have been using ABM to simulate cell and molecule interactions for the investigation of the patterns of various tissue growth. [41][42][43] We use an idealized model of tissue regeneration following damage to demonstrate the application of CppyABM (see Figure 4). In this model, a square simulation domain consisting of a 1000 × 1000 grid is created, where each patch has a length of 15 μm which corresponds to the average cell size and only accommodates one agent at a time.…”
Section: Agent-based Simulation Of Cellular Interactionsmentioning
confidence: 99%
“…In recent years, an increasing number of studies have been using ABM to simulate cell and molecule interactions for the investigation of the patterns of various tissue growth 41–43 . We use an idealized model of tissue regeneration following damage to demonstrate the application of CppyABM (see Figure 4).…”
Section: Showcases Of Cppyabmmentioning
confidence: 99%